Assessment of the application for renewal of authorisation of Lantharenol® (lanthanum carbonate octahydrate) for cats. (11th January 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Lantharenol ® is a feed additive consisting of lanthanum carbonate octahydrate. It is currently authorised as a zootechnical additive (decrease in phosphorous excretion via urine) for cats; this opinion concerns the renewal of the authorisation. In 2007, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) adopted an opinion on the safety and efficacy of Lantharenol ® as a feed additive for cats. The applicant has provided data demonstrating that the additive complies with the conditions of authorisation. The available evidence, including the results of the post‐market monitoring plan, confirms that the use of Lantharenol ® in cat food at the maximum authorised concentration of 7.5 g/kg of complete feed is safe for cats. In the absence of new data, the FEEDAP Panel reiterates its previous conclusion that Lantharenol ® does not pose a risk by inhalation and is not an irritant to skin or eye and not a dermal sensitiser. The FEEDAP Panel considers that there is no need for a continuation of a specific post‐market monitoring plan.